Ubiquitin‐Specific Peptidase 10 (USP10) Inhibits Hepatic Steatosis, Insulin Resistance, and Inflammation Through Sirt6. Issue 5 (17th September 2018) - Luo, Pengcheng; Qin, Cong; Zhu, Lihua; Fang, Chun; Zhang, Yan; Zhang, Hai; Pei, Fei; Tian, Song; Zhu, Xue‐Yong; Gong, Jun; Mao, Qing; Xiao, Chengcheng; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis, insulin resistance and inflammation, and the pathogenic mechanism of NAFLD is poorly understood. Ubiquitin‐specific peptidase 10 (USP10), a member of the ubiquitin‐specific protease family, is involved in environmental stress responses, tumor growth, inflammation, and cellular metabolism. However, the role of USP10 in hepatic steatosis, insulin resistance, and inflammation remains largely unexplored. USP10 expression was detected in livers of patients with NAFLD, mice with high‐fat diet (HFD)‐induced obesity, and genetically obese (ob/ob) mice, as well as in palmitate‐induced hepatocytes. The function of USP10 in hepatic steatosis, insulin resistance, and inflammation was investigated using hepatocyte‐specific USP10 deficiency or overexpression in mice induced by HFD treatment or genetic defect. The molecular mechanisms underlying USP10‐regulated hepatic steatosis were further investigated in HFD‐treated mice. USP10 expression was significantly decreased in the fatty livers of NAFLD patients and obese mice and in palmitate‐treated hepatocytes. USP10 deficiency exacerbated the metabolic dysfunction induced by HFD treatment for 12 weeks. Conversely, USP10 overexpression significantly suppressed metabolic dysfunction in mice after HFD treatment and inhibited the development of NAFLD in ob/ob mice. Further investigation indicated that USP10 regulates hepatic steatosis by interacting with Sirt6 and inhibiting its ubiquitination and degradation. Sirt6 overexpression markedly ameliorated the effects of USP10 deficiency in hepatic steatosis, insulin resistance, and inflammation. Conversely, Sirt6 deficiency decreased the ameliorative effects of USP10 overexpression in response to HFD treatment. Conclusion: USP10 inhibits hepatic steatosis, insulin resistance, and inflammation through Sirt6.